Rest Well Sdn Bhd / Nurul Syahirah Hasbi - Hasbi, Nurul Syahirah (2020)
Our company provides customers with a cushion that have many functions called Multi- Function Cushion especially for those who often use laptop or phone while lying down. This cushion combine the design of cushion and briefcase. The height of Multi- Function Cushion can be change according to the user comfort but it still follow the right body position. It also have a function to store any valuable things and have security measures where on the handle, there is a hand scanner and on the side of the briefcase, there is a fingerprint function. It also can be used as a laptop stand which can be placed on thighs.